Strategi Kepala Sekolah: Mengoptimalkan Kinerja Guru melalui Pembiasaan Perilaku Kedisiplinan - Ridwanulloh, M. Ubaidillah; Nugroho, Putra Bintan Adi; Rochmah, Naila Nur; Nurfadhilah, Rizqi; Fernanda, Yolla; Muna, Rif’atul (STAI Muhammadiyah Paciran Lamongan, 2024)
Generally, schools with good quality and reputation have a high level of work culture and discipline. However, not all school principals are capable of forming a disciplined work culture. In fact, they tend to overlook teacher discipline behavior. SMAN 7 Kota Kediri is one of the quality educational institutions that has been able to achieve various achievements. It turns out that the quality and achievements of educational institutions are due to the principal's establishment and habituation of disciplined behavior within the school organization. The research method used in this study is qualitative method. Data was obtained using interview, observation, and documentation methods. The results of the study indicate that the progress of SMAN 7 Kota Kediri is obtained due to disciplined behavior and becomes a school culture. In forming a disciplinary culture, the principal uses methods in several stages starting from: consistent socialization of disciplinary policies in evaluation meetings, forming teams to monitor the implementation of disciplinary behavior in the field, optimizing disciplinary behavior using checklock attendance tools, and giving preventive and curative sanctions to teachers who violate disciplinary policies. In order for disciplinary behavior to become a school disciplinary culture, the principal sets an example and provides exemplary behavior in every activity at school. In conclusion, the principal's strategy in optimizing teacher performance through habituation of disciplinary behavior runs effectively and successfully formed in the school organization as a work culture system.